2000
DOI: 10.1128/mcb.20.17.6233-6243.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Chaperone Activity of Simian Virus 40 Large T Antigen Is Required To Disrupt Rb-E2F Family Complexes by an ATP-Dependent Mechanism

Abstract: The simian virus 40 large T antigen (T antigen) inactivates tumor suppressor proteins and therefore has been used in numerous studies to probe the mechanisms that control cellular growth and to generate immortalized cell lines. Binding of T antigen to the Rb family of growth-regulatory proteins is necessary but not sufficient to cause transformation. The molecular mechanism underlying T-antigen inactivation of Rb function is poorly understood. In this study we show that T antigen associates with pRb and p130-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 52 publications
5
93
0
Order By: Relevance
“…One model is that T antigen ®rst binds to Rb/E2F complexes through its LXCXE motif and then these complexes are dissolved using energy derived from hsc70-mediated ATP hydrolysis (Srinivasan et al, 1997). In fact, puri®ed T antigen has been shown to bind p130/E2F-4 and pRb/E2F-4 complexes in vitro and the dissolution of these complexes requires ATP hydrolysis by hsc70 (Sullivan et al, 2000a). This explains why the J domain is required in addition to the LXCXE motif to e ect E2F transcriptional activation.…”
Section: T Antigens Target Key Cellular Regulatory Proteins To E Ect mentioning
confidence: 99%
“…One model is that T antigen ®rst binds to Rb/E2F complexes through its LXCXE motif and then these complexes are dissolved using energy derived from hsc70-mediated ATP hydrolysis (Srinivasan et al, 1997). In fact, puri®ed T antigen has been shown to bind p130/E2F-4 and pRb/E2F-4 complexes in vitro and the dissolution of these complexes requires ATP hydrolysis by hsc70 (Sullivan et al, 2000a). This explains why the J domain is required in addition to the LXCXE motif to e ect E2F transcriptional activation.…”
Section: T Antigens Target Key Cellular Regulatory Proteins To E Ect mentioning
confidence: 99%
“…This dissociation requires Hsc70, ATP and a functional J domain (Sullivan et al, 2000a). The mechanism of T-antigen J-domain-mediated inhibition of pRb2/p130 phosphorylation has also been investigated.…”
Section: Interaction Of Sv40 Large T-antigen With Prb and Its Family mentioning
confidence: 99%
“…It has been demonstrated that JCV T-Ag, like its simian counterpart SV40, binds pRb family members and influences their phosphorylation status and stability (Dyson et al, 1990;Howard et al, 1998). On the contrary, JCV T-Ag interaction with Hsc70 has only been shown using chimeric JCV-SV40 T-Ag (Sullivan et al, 2000b). Large T antigen J domains of JCV and SV40 are highly homologous (Pipas, 1992).…”
Section: Prb-t-ag Interactionmentioning
confidence: 99%